Differentiated Instruction in Teaching Vocabulary: Senior High School in Indonesia - Nurmalayanti Amar; La Sunra; Nur Aeni (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study investigates the effectiveness of Differentiated Instruction (DI) in enhancing English vocabulary acquisition among senior high school students in Indonesia. Recognizing the varied learning styles, interests, and readiness levels among learners, DI offers a flexible approach tailored to individual needs. A quasi-experimental design with pre-test and post-test was employed, involving an experimental group taught using DI and a control group taught using conventional methods. Data were collected through vocabulary tests and a student engagement questionnaire. The results revealed that students in the DI group demonstrated significantly higher vocabulary mastery and greater engagement in the learning process compared to those in the control group. These findings suggest that Differentiated Instruction is a promising strategy to support vocabulary development and foster active participation in English language learning at the secondary education level.